DINAMIKA KELOMPOK TANI BEA WAJA KELURAHAN PAGAL KECAMATAN CIBAL KABUPATEN MANGGARAI - Oskarianus Ondok; Selfius P. N. Nainiti; Lika Bernadina (Undana Press, 2021)
This research was conducted in Pagal Village, Cibal District, Manggarai Regency in February 2020 with the aim of knowing the dynamics of farmer groups and the relationship of socio-economic factors to the dynamics of farmer groups. The location was determined purposively (purposive sampling) on ​​the basis of the consideration that there was no research related to group dynamics at that location. Respondents were determined by census therefore all 34 members of the Bea Waja farmer group were used as respondents. Results of data analysis The dynamic level of the Bea Waja Farmer Group was in the high category with an average score achievement of 2,79 or 93.00%, the element that gave the highest assessment was the element of group objectives, namely 98% with an average score of 2,95 while The element that gave the smallest assessment was the group structure element, namely 88% with an average score of 2,64 There was no significant relationship between socio-economic factors and the dynamics of the Bea Waja Farmer Group. This happened because all members of the Bea Waja Farmer Group gave the same value to the dynamic elements of the group even though the category of factors for age, education level, number of family dependents and length of farming were different.